2014
DOI: 10.2478/folmed-2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Serum Levels of Thyroid-Stimulating Hormone and Anti-Thyroid Peroxidase Antibodies, Age and Gender on Depression as Measured by the Zung Self-Rating Depression Scale

Abstract: The depressive score was higher in the females and increased with age. Hypothyroidism determined a higher risk of depression in the females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…To analyze group differences in demographic and clinical variables, we performed analysis of variance [ 38 ] for continuous variables (i.e., age, TICV, and HDRS scores) and chi-squared tests for categorical variables (i.e., sex, educational level, family history, mood state, and drug treatment). We also performed t-tests to compare illness duration and psychiatric scale scores, including the YMRS, Korean version of the Mood Disorder Questionnaire, Hamilton Anxiety Rating Scale, and Barratt Impulsiveness Scale scores, between the BD I and BD II groups.…”
Section: Methodsmentioning
confidence: 99%
“…To analyze group differences in demographic and clinical variables, we performed analysis of variance [ 38 ] for continuous variables (i.e., age, TICV, and HDRS scores) and chi-squared tests for categorical variables (i.e., sex, educational level, family history, mood state, and drug treatment). We also performed t-tests to compare illness duration and psychiatric scale scores, including the YMRS, Korean version of the Mood Disorder Questionnaire, Hamilton Anxiety Rating Scale, and Barratt Impulsiveness Scale scores, between the BD I and BD II groups.…”
Section: Methodsmentioning
confidence: 99%
“…This finding was supported by the results of a cohort study showed that about 69% (n=44) out of 64 untreated hyperthyroid had depression and 46% (n=29) from this group had persisted depression even after the treatment (7). This is in contrast to the findings reported from the three descriptives studies which found that the high prevalence of depression was among hypothyroid patients (45,47,48). Furthermore, the significant correlation between depression and type of thyroid disorders found (p=0.01) (46).…”
Section: Discussionmentioning
confidence: 58%
“…It means the higher of the TSH level, the stronger to had depression. This evidence was supported by population-based at Bulgaria that showed the significant association between the TSH level and depression was among participants who had high level of TSH (p=0.026) (48). However, some studies were failed to showed the association between these two variables (1,2,49).…”
Section: Discussionmentioning
confidence: 82%
“…After exclusion of duplicates, 3372 were screened and out of those, 62 were assessed for eligibility in full text. Fifteen studies [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] are included in this meta-analysis (PRISMA flowchart, Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…In fourteen studies effects for both, hyper-and hypothyroidism were reported [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Thomsen et al published corresponding data on hypothyroidism in a separate study [46].…”
Section: Resultsmentioning
confidence: 99%